2005
DOI: 10.1073/pnas.0503630102
|View full text |Cite
|
Sign up to set email alerts
|

MLL associates specifically with a subset of transcriptionally active target genes

Abstract: MLL (mixed-lineage leukemia) is a histone H3 Lys-4 specific methyltransferase that is a positive regulator of Hox expression. MLL rearrangements and amplification are common in acute lymphoid and myeloid leukemias and myelodysplastic disorders and are associated with abnormal up-regulation of Hox gene expression. Although MLL is expressed throughout hematopoiesis, Hox gene expression is sharply down-regulated during differentiation, suggesting that either the activity of MLL or its association with target prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
189
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(212 citation statements)
references
References 43 publications
(54 reference statements)
16
189
1
1
Order By: Relevance
“…Furthermore, overexpression of HOXA5 acts on myeloid proliferation and differentiation (Crooks et al, 1999). MLL was shown to regulate directly HOX gene expression (Yu et al, 1995;Milne et al, 2002Milne et al, , 2005Hsieh et al, 2003;Ernst et al, 2004;Dou et al, 2005). In our present study, ChIP experiments in CD34 þ cells indicate that both MLL and MOZ are recruited to HOXA5, HOXA7 and HOXA9 promoters, which correlates with the detection of activation epigenetic marks, such as H3K9K14ac, H4K16ac, H3K4me2 and H3K4me3.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Furthermore, overexpression of HOXA5 acts on myeloid proliferation and differentiation (Crooks et al, 1999). MLL was shown to regulate directly HOX gene expression (Yu et al, 1995;Milne et al, 2002Milne et al, , 2005Hsieh et al, 2003;Ernst et al, 2004;Dou et al, 2005). In our present study, ChIP experiments in CD34 þ cells indicate that both MLL and MOZ are recruited to HOXA5, HOXA7 and HOXA9 promoters, which correlates with the detection of activation epigenetic marks, such as H3K9K14ac, H4K16ac, H3K4me2 and H3K4me3.…”
Section: Discussionsupporting
confidence: 68%
“…Alternatively, MLL could be regulated by modulating its binding. As reported by Milne et al (2005), MLL is associated with actively transcribed target genes, but does not remain bound after transcriptional downregulation.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The presence of SET1/TRX-type proteins, H3K4me3, and Ser5P in 59 regions of transcriptionally active genes has been observed in yeast, mammals, and plants (Ng et al, 2003;Milne et al, 2005;Kim et al, 2008). Although an earlier study has suggested that Ser5P was essential for transcription in yeast (Valay et al, 1995), recent evidence shows that phosphorylation of Ser5P is not required for transcription in yeast (Kanin et al, 2007).…”
Section: Discussionmentioning
confidence: 93%
“…13,14 In several studies, direct binding of the der(11)-encoded MLL fusion protein to promoter regions of the above-mentioned genes has been demonstrated by ChIP (chromatin immunoprecipitation) experiments). 13,[15][16][17] This indicates that MLL fusion proteins encoded by the der (11) chromosome are able to influence directly the transcription of specific target genes.…”
Section: Introductionmentioning
confidence: 99%